A Real-Time Web Information System Based on A Global Positioning System for Monitoring Environmental Pollution - Eko Gustriyadi; Volvo Sihombing; Masrizal Masrizal; Puput Dani Prasetyo Adi (Kresnamedia Publisher, 2022)
This research will discuss monitoring pollution in waterways in real time based on GPS. A website-based information system is an essential factor for information media, not only database-based but can be communicated with GPS. GPS is a satellite system that can determine the point of an area with Longitude and Latitude parameters. The Global Positioning System is one of the parameters used in this study. Longitude and Latitude are the primary keys to getting the point in a particular area or point. In research, this is the location used in sensor or environmental pollution monitoring. In this paper, we try to review the projects carried out and perform analysis, management, and governance on the server and local host. The program is made by developing the FrontEnd and BackEnd sides. Development can be done on Desktop-based programming and then extended to Mobile by manipulating and modifying programs using Javascript, JSON, and other building scripts for better performance and suitable for deployment on various platforms such as Mobile-based. This system is very efficient in determining various parameters, for example, the environmental pollution factor. From testing, the GPS data is not perfect, all data can be sent, but the accuracy of GPS data can reach 96%. This is due to data errors during uplinking and downlinking data.